Desempenho operacional e energético de um microtrator em função da lastragem, velocidade de deslocamento e pressão de inflação dos pneus - Araújo, Karla Lúcia Batista (2013)
The microtractor is ideal for activities in small areas by optimizing the work. The experiment was conducted at the Federal University of Ceará in order to evaluate the energy efficiency and operating a mechanized set microtractor rotoencanteirador-in three-speed, inflation pressure and tire ballast, with and without ballast. To obtain data for energy efficiency used a microtractor, instrumented with inductive sensors to measure wheel slippage, beakers to measure the fuel consumption and load cell for the workforce in the drawbar. The variables studied were working speed skating rotated, hourly fuel consumption, specific fuel consumption, power drawbar pull and power available. We conducted two factorial experiments for each variable evaluated, the first with microtractor without ballast and another with the use of weights, each experiment consisted of two factors: gears (1st, 2nd and 3rd) and inflation pressure of tires (82,74; 96,53 and 110,32 kPa). Data were subjected to analysis of variance test was used for comparison Tukey test at 5% significance level using the Software Assistat 7.6. The highest values were found with speeds microtractor working without ballast in third gear. The largest slip was found in third gear with microtractor without ballast and for different pressures was unbacked pressure of 82,74 kPa. The highest hourly consumption was recorded in third gear without ballast to the pressures of 96,53 kPa was without ballast. For the specific consumption the highest value was 3483.04 g.kW-1.h-1, with microtractor backed and 3267,48 g.kW-1.h-1 at a pressure of 82,74 kPa. The tensile strength in first gear was 6,02 kN, 4,81 kN in the second and third of 3,2 kN, all did not change with the change of pressure, working without ballast. Backed force was 4,81 kN, 3,2 kN and 2,00 kN in the first, second and third gear respectively. The greatest power was found in second gear without ballast. Among the most pressure was 0,48 kW at a pressure of 82,74 kW. The largest land area of 0,082 m2 was mobilized in first gear with 96,53 kPa when working without ballast. With the ballast was the largest area of 0,82 m2 in first gear with 82,74 kPa. The best efficiency of the system was in first gear to 82,74 kPa backed, 74.56%.